Some Result about a Product of Conjugate Cycles - Al-Bundi, Shaimaa Salman (Al-Nahrain Journal of Science, 2011)
الخلاصة:The aim of this paper is to give a generalization of the theorem that, for n  5, every even permutation defined on n symbols is commutator a b a-1 b-1 of even permutations a and b. In particular, [3n/4]  L  n is shown to be the necessary and sufficient condition on L, in order that every even permutation defined on n  5 symbols can be expressed as a product of two cycles, each of length L. Results follow, including every odd permutation is a product of a cycle of length L and a cycle of length L + 1.